Etika Pengelolaan Sumber Daya Alam Berkelanjutan Dalam Perspektif Islam - Fadli, Zawil; Sarjan, Muhammad (Lamda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2024)
This article discusses the importance of ethics in sustainable management of natural resources from an Islamic perspective. With a focus on environmental conservation and sustainability of natural resources, this research highlights the ethical principles that must be applied in natural resource management. From an Islamic perspective, the earth and its contents are seen as a gift from Allah that must be protected and used wisely for human welfare and survival. By understanding and applying these ethical principles, it is hoped that sustainability goals can be achieved in managing natural resources for human welfare and environmental sustainability.